Association between caregiver depression and child after-school program participation. Issue 3 (27th May 2021) - Daly, Nora J.; Parsons, Michael; Blondino, Courtney; Clifford, James S.; Prom-Wormley, Elizabeth
ABSTRACT: Depressive symptoms in parents and caregivers to children are associated with adverse biopsychosocial outcomes for caregivers themselves and the children in their custody. Higher overall and parenting-related stress, including stress over children's unsupervised after-school time, is associated with increased caregiver depression risk. Child after-school program participation is a form of social support that may mitigate parenting-related stress and reduce caregiver depression risk. This study tested for the association between child after-school program participation and caregiver depression in a sample of 486 caregivers in Richmond, Virginia. Child after-school program participation was associated with a significant reduction in the likelihood of a past caregiver depression diagnosis (OR = 0.58, 95% CI = 0.39– 0.86, p = .007). This relationship remained significant after adjusting for the influence of caregiver anxiety, stress, financial hardship, and sociodemographic characteristics (OR = 0.49, 95% CI = 0.27– 0.86, p = .015). Child after-school program participation may function as a protective factor that reduces caregiver depression risk. More research is needed to determine whether the observed association is causal in nature and dosage dependent. Findings from this and future studies may be used to inform evaluation of the impact of after-school programs at the family-level.